Sosialisasi Personal Hygiene dan Pencegahan Penyakit Scabies di Pondok Pesantren Abdurrahman Bin’ Auf Kendari - Anesta, Resqy Nongri; Bahar, Hartati; Effendy, Devi Savitri; Muchtar, Febriana; Lestari, Hariati; Tosepu, Ramadhan; Haliza, Nur; Marfi, Wa Ode Elsa; Liawati, Leli; Jayanti (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Scabies is a contagious skin disease caused by infected and easily transmitted Sarcoptes scabiei var hominis mites and often occurs in high-density environments, such as Islamic boarding schools. One of the main causes of scabies is personal hygiene. Personal hygiene, also known as personal hygiene, is maintaining physical and mental cleanliness and health. Low knowledge and awareness of personal hygiene among students can increase the risk of this disease. The purpose of the counseling activity is to increase knowledge about personal hygiene and scabies among students at the Abdurrahman bin 'Auf Kendari Islamic boarding school. The method used is lectures and educational games using true and false boxes and mystery boxes. The number of participants in this education was 53 students. The results of the socialization showed that there was a difference in average knowledge before and after being given education with a statistical test using the Paired t-test. So it can be concluded that socialization of personal hygiene and scabies can increase student knowledge.